Job meaningfulness, employee engagement, supervisory support and job performance: a moderated-mediation analysis. Issue 6 (27th August 2021) - Panda, Abinash; Sinha, Subhashis; Jain, Nikunj Kumar
Abstract : Purpose: Guided by social exchange, broaden and build and conservation of resources theoretical perspectives, this study explores the moderated mediating role of supervisory support (SS) on the relationship between job meaningfulness (JM) on job performance (JP) through employee engagement (EE). Design/methodology/approach: Field data were collected from two hundred and nineteen executives and their thirty-eight supervisors of a large paint manufacturing industry through a time-lagged research design and was analyzed with partial least squares based structural equation modeling. Findings: Findings of this study indicate that JM mediated by EE contributes to JP, which means if an employee finds one's job meaningful, she/he is likely to be more engaged emotionally, psychologically and cognitively to deliver better JP. SS is also found to be salient as it moderates both direct and indirect relationships between JM and JP through EE. Research limitations/implications: Generalizability of the findings of this study should be done with caution. Though the study has time-laggard data from two different sources but missing longitudinal data restricts causality of relationships/findings. Practical implications: These findings are relevant for organizations given that organizational leaders can create a context, by appropriate job design and engaging work context that motivates employees to perform better in their jobs. Insights of this study will be useful for organizations to curate meaningful jobs for their employees and also groom leaders with requisite skills and competencies to help subordinates perform up to their potential. Originality/value: This study is an attempt toward a better understanding of the interplay of JM, work engagement and SS on JP in a manufacturing set-up in India, which has not been hitherto examined in Indian context.